Thyroid dysfunction in type 2 diabetes mellitus patients attending diabetic clinic in a tertiary care centre: a cross-sectional study - Jamatia, Bithika; Debbarma, Rajesh K.; Majumdar, Tapan (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Thyroid disease and type 2 diabetes mellitus are two common co-existing endocrinopathies found in the general population. Since thyroid dysfunction complicates the metabolic derangement observed in diabetes, its treatment is necessary in order to achieve stability of metabolic control. Therefore, the aim of the present investigation was to estimate the functional thyroid disorders and the associated factors in type 2 diabetes patients. Methods: In 230 diabetic patients, the blood sugar level and thyroid function tests were performed and compared. Most of the patients were in the age group of 51-60 years (36.08%). Results: The prevalence of thyroid dysfunction in diabetic patients was 15.21% with a higher rate in female patients. Subclinical hypothyroidism (12.17%) was the commonest thyroid dysfunction. Conclusions: The data suggest that subclinical hypothyroidism was more prevalent in type 2 diabetes mellitus, and may confer a greater risk of diabetic complications. It is therefore important to diagnose thyroid dysfunction in diabetic patients and the practice should be inculcated in diabetic care.